The spirit of early Christian thought : seeking the face of God - Wilken, Robert Louis, 1936- (New Haven : Yale University Press, 2003)
Written by a religious historian, this is an introduction to early Christian thought. Focusing on major figures such as St Augustine and Gregory of Nyssa, as well as a host of less well-known thinkers, Robert Wilken chronicles the emergence of a specifically Christian intellectual tradition. In chapters on topics including early Christian worship, Christian poetry and the spiritual life, the Trinity, Christ, the Bible, and icons, Wilken shows that the energy and vitality of early Christianity arose from within the life of the Church. While early Christian thinkers drew on the philosophical and rhetorical traditions of the ancient world, it was the versatile vocabulary of the Bible that loosened their tongues and minds and allowed them to construct the world anew, intellectually and spiritually. These thinkers were not seeking to invent a world of ideas, Wilken shows, but rather to win the hearts of men and women and to change their lives. Early Christian thinkers set in place a foundation that has endured. Their writings are an irreplaceable inheritance, and Wilken shows that they can still be heard as living voices within contemporary culture. --
Introduction -- Founded on the cross of Christ -- An awesome and unbloody sacrifice -- The face of God for now -- Seek his face always -- Not my will but thine -- The end given in the beginning -- The reasonableness of faith -- Happy the people whose God is Lord -- The glorious deeds of Christ -- Making this thing other -- Likeness to God -- The knowledge of sensuous intelligence
Includes bibliographical references (p. 341-352) and indexes
Keywords: Church history -- Primitive and early church, ca. 30-600; Theology -- History -- Early church, ca. 30-600